2019
DOI: 10.21203/rs.2.12475/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for mortality of patients with ceftriaxone resistant e. Coli bacteremia receiving carbapenem versus beta lactam/beta lactamase inhibitor therapy

Abstract: Objective: Extended spectrum β-lactamases (ESBL) producing Enterobacteriaceae predominantly E. coli and K. pneumoniae bacteremia have limited treatment options and high mortality. The objective was to determine the risk factors for in-hospital mortality particularly treatment with Carbapenem versus Beta lactam/beta lactamase combination (BL/BLI) in patients with Ceftriaxone resistant E. coli bacteremia. A retrospective cohort study was conducted at the Aga Khan University, Karachi, Pakistan. Adult patients wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The most common bacteria causing sepsis is Escherichia coli (E. coli). The emergence of extended spectrum beta lactamase (ESBL) producing E. coli leads to the therapeutic failure and excess mortality [4,5]. The previous studies reported that the incidence of ESBL producing E. coli infection in England was 10%, there were 925 cases of ESBL producing E. coli infection in USA noted by The Duke Infection Control Outreach Network and there were 883 cases of ESBL producing E. coli infection in Thailand and the incidence tends to increase every year.…”
Section: Introductionmentioning
confidence: 99%
“…The most common bacteria causing sepsis is Escherichia coli (E. coli). The emergence of extended spectrum beta lactamase (ESBL) producing E. coli leads to the therapeutic failure and excess mortality [4,5]. The previous studies reported that the incidence of ESBL producing E. coli infection in England was 10%, there were 925 cases of ESBL producing E. coli infection in USA noted by The Duke Infection Control Outreach Network and there were 883 cases of ESBL producing E. coli infection in Thailand and the incidence tends to increase every year.…”
Section: Introductionmentioning
confidence: 99%